A randomised double-blind placebo-controlled feasibility trial of flavonoid-rich cocoa for fatigue in people with relapsing and remitting multiple sclerosis. Issue 5 (4th March 2019) - Coe, Shelly; Cossington, Jo; Collett, Johnny; Soundy, Andrew; Izadi, Hooshang; Ovington, Martin; Durkin, Luke; Kirsten, Maja; Clegg, Miriam; Cavey, Ana; Wade, Derick T; Palace, Jacqueline; et al.
Abstract : The impact of flavonoids on fatigue has not been investigated in relapsing and remitting multiple sclerosis (RRMS). Objective: To determine the feasibility and estimate the potential effect of flavonoid-rich cocoa on fatigue and fatigability in RRMS. Methods: A randomised double-blind placebo-controlled feasibility study in people recently diagnosed with RRMS and fatigue, throughout the Thames Valley, UK (ISRCTN69897291 ). During a 6-week intervention participants consumed a high or low flavonoid cocoa beverage daily. Fatigue and fatigability were measured at three visits (weeks 0, 3 and 6). Feasibility and fidelity were assessed through recruitment and retention, adherence and a process evaluation. Results: 40 people with multiple sclerosis (10 men, 30 women, age 44±10 years) were randomised and allocated to high (n=19) or low (n=21) flavonoid groups and included in analysis. Missing data were <20% and adherence to intervention of allocated individuals was >75%. There was a small effect on fatigue (Neuro-QoL: effect size (ES) 0.04, 95% CI −0.40 to 0.48) and a moderate effect on fatigability (6 min walk test: ES 0.45, 95% CI −0.18 to 1.07). There were seven adverse events (four control, three intervention), only one of which was possibly related and it was resolved. Conclusion: A flavonoid beverage demonstrates the potential to improve fatigue and fatigability in RRMS.